Rural communities’ vulnerability to farmland poverty in varied ecological settings of northwest Ethiopia - Menberu Teshome (Journal of Degraded and Mining Lands Management, 2018)
Environmental and climate changes are among the serious threats to the world’s land resources in the 21st Century. Particularly, in the developing countries the impact inevitably goes as the continuing toll on agricultural production, human lives, and properties. It is also a driving force of poverty and impediment of overall economic development in many less developed nations, like Ethiopia. Therefore, this paper assesses the rural communities’ vulnerability to farmland poverty in different ecological settings of northwest Ethiopia. Data were collected from 525 randomly selected farming households using questionnaire. Meteorological data were collected from Global Weather Data for soil and water assessment tool (SWAT) from 1979 to 2010. Rainfall and temperature trends were characterized using simple linear regression model. Rural communities’ vulnerability to farmland poverty was determined using livelihood vulnerability index (LVI). Indices were constructed using simple and weighted average approaches to measure farmlands’ exposure, sensitivity and adaptive capacity. Overall communities’ levels of vulnerability to farmlands poverty were found to be 0.76 in the lowland, 0.57 in the flat highland and 0.51 in the midland areas. In almost all indicators the lowland (Abay Valley) is more vulnerable to farmland-related troubles as the biophysical and socio-economic contexts were found to be the worst there. Communities and government and non-government officials have observed significant negative impacts of drought and extreme weather events on farmlands, pasturelands with declining availability, productivity and quality of farmlands. This study suggests education and research interventions for enhancing community-based participatory integrated watershed management approach supported with best indigenous knowledge and farmers’ practices. Adaptation interventions should also consider local communities’ resource capacity (low-cost investment in sound farmland and soil management techniques).